Greening the Bottom Line: How Do Banking Sectors Implement Technology to Support Sustainable Development Goals in Innovation? - Gunawan, Juniati; Ambarita, Indah Olivia; Putri, Aghnia Nadhira Aliya; Lee, John Chuan Guan (International Journal of Entrepreneurship and Sustainability Studies, 2024)
The urgent need to align banking practices with the Sustainable Development Goals (SDGs) has become increasingly apparent, particularly in the context of fostering industry, innovation, and infrastructure. The primary issue at hand is the insufficient integration of SDG 9 into banks’ core strategies and operations, despite its critical importance for sustainable development. The novelty of this study lies in its detailed examination of the extent to which Indonesian banks support SDG 9 through their reported activities, an area that has been underexplored in previous research. This research aimed to investigate the level of support from banking industries to the Sustainable Development Goals (SDGs), with a particular focus on SDG 9: industry, innovation, and infrastructure. This study utilized a content analysis approach to collect secondary data from the sustainability reports of 44 banks listed on the Indonesia Stock Exchange between 2017 and 2020, resulting in 176 observations. In cases where sustainability reports were unavailable, annual and combined reports were used as unit analyses. The findings revealed that Indonesian banks have undertaken various activities to support SDGs, and there has been an increasing trend in disclosure from 2017 to 2020. However, the study found that a significant role of technology transformation, which should lead to innovation and support for SDG 9, was lacking. This finding suggests that SDGs are still primarily measured by external activities rather than internal activities, despite the importance of business strategy in supporting SDGs. Another significant finding was that micro, small, and medium enterprises (MSMEs) received the most support for sustainable business activity categories (SBAC). The research contributes to the literature by providing insights into the level of support for SDG 9 and SBACs. The study also underscores the importance of measuring the impact of digital banking services, which have been widely implemented, and the need for significant support for SBAs in the environmental sector.